2022
DOI: 10.1111/1468-5973.12447
|View full text |Cite
|
Sign up to set email alerts
|

Debunking misinformation in times of crisis: Exploring misinformation correction strategies for effective internal crisis communication

Abstract: This study aimed to explore misinformation correction strategies for effective internal crisis communication. Using an experimental study (N = 1196) with full‐time employees in the United States, this study found that a corrective strategy using more elaborated facts was effective in protecting internal reputation and that timely, proactive communication to debunk crisis misinformation was a significant factor influencing employees' cognitive reactance (counterarguing) and behavioural outcomes. This research c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 79 publications
(221 reference statements)
2
3
0
Order By: Relevance
“…This finding strongly substantiates that if organizations accept wrong doing and provide employees with factual information about a crisis situation, it can significantly increase positive support and identification with the organization. This finding supports previous studies (Adamu & Mohamad, 2019b; Kim & Lim, 2023) about the positive effect of internal communication on crisis responsibility. These studies enunciated the importance of ethical‐based responses by providing factual information, supporting SCCT's position that all crises should begin with ethical responses (Coombs, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding strongly substantiates that if organizations accept wrong doing and provide employees with factual information about a crisis situation, it can significantly increase positive support and identification with the organization. This finding supports previous studies (Adamu & Mohamad, 2019b; Kim & Lim, 2023) about the positive effect of internal communication on crisis responsibility. These studies enunciated the importance of ethical‐based responses by providing factual information, supporting SCCT's position that all crises should begin with ethical responses (Coombs, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…This finding supports previous studies (Adamu & Mohamad, 2019b;Kim & Lim, 2023) about the positive effect of internal communication on crisis responsibility. These studies enunciated the importance of ethical-based responses by providing factual information, supporting SCCT's position that all crises should begin with ethical responses (Coombs, 2020).…”
Section: Theoretical Implicationsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, the trustworthiness of information, open communication and trust have been identified as crucial factors for effective postpandemic recovery for the tourism industry (Yeh, 2021). For example, issues such as fake news and echo chambers in social networks are being increasingly debated and investigated within the field of crisis communication research (Cheng & Lee, 2019; Jahng, 2021; Jin et al, 2020; Kim & Lim, 2022; Mehta et al, 2021). THCCR can significantly benefit from building synergies with this stream of research.…”
Section: Developing a Future Research Agendamentioning
confidence: 99%
“…More importantly, Kim (2020) noted that employee information-seeking behaviours should involve searching for and acquiring vital organizational information from co-workers and external audiences for effective internal communication. More recently, Kim and Lim (2023) reported that proactive communication IJPPM 73,7 favors employee sensemaking. Thus, organizational management needs to ensure effective communication that allows employees to understand the unfolding crisis situation.…”
Section: Communication Behaviour For Sensemakingmentioning
confidence: 99%